Sherpa: Stories of Life and Death from the Guardians of Everest - Bashyal, Pradeep (London Carmelite House, 2023)
Amid all the foreign adventurers that throng to Nepal to scale the world's highest peaks there exists a small community of mountain people at the foothills of Himalayas. Sherpa tells their story. It's the story of endeavour and survival at the roof of the world. It dives into their culture and tells of their existence at the edge of life and death. Written by Ankit Babu Adhikari - a writer, social science researcher and musician - and Pradeep Bashyal - a journalist with the BBC based in Nepal - Sherpa traces their story pre- and post-mountaineering revolution, their evolution as climbing crusaders with previously unpublished stories from the most notable and incredible Sherpas of the last 50 years.
Keywords: Becoming Sherpa